Studi Karakteristik Aliran Udara Kendaraan dengan Penambahan Spoiler Belakang Standard Dan Lebih Panjang - Kurniawan, Moch. Aziz; Oktopianto, Yogi; Eska Fahmadi, Aat; Rusmandani, Pipit (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2022)
The use of rear spoilers on MPV vehicles is often used by the public to get an aerodynamic vehicle body design. The understanding of the function of using rear spoiler accessories in the community is still low, so it is necessary to study the characteristics of air flow in aerodynamics. This study aims to determine the flow characteristics of MPV type vehicles with standard and longer rear spoiler installation. This research was conducted in a Subsonic Open Circuit wind tunnel with test section dimensions (365 x 365 x 1250) mm. The flow characteristics were observed experimentally that passed through the model surface resembling the first generation Toyota Avanza MPV with a ratio of 1:20 with variations of the standard and longer rear spoiler installation. Measurement of the flow velocity profile behind the vehicle test model was carried out at an X/L ratio of 0.32 from the leading edge with a speed adjusted to the Reynolds number value of 1.96 x 105. The flow characteristic observed was the pressure distribution (Cp) on the center line of the top surface. and under the test vehicle model, the flow momentum deficit behind the test vehicle model, the lift pressure coefficient (CLP), and the drag pressure coefficient (CDP). The results of data collection show that the installation of a standard and longer rear spoiler relatively increases the Cp value, the flow momentum deficit behind the vehicle model, the lift pressure coefficient (CLP) value and decreases the drag pressure coefficient (CDP) value. The biggest increase was in the installation of a longer rear spoiler with an increase in the Cp value of 4.7%, an increase in the flow momentum deficit by 1.27%, an increase in the CLP value by 0.11% and a decrease in the CDP value by 0.06% compared to the vehicle model without using a rear spoiler.